Prevalence of Brucella in dogs in China: a systematic review and meta-analysis—Epidemiological analysis of canine brucellosis - Xiang, Mei-Mei; Jiang, Hong-Yun; Jiang, Qiu-chi; Zhang, Yi-fan; Yu, Jia-yu; Li, Lian-Min; Wang, Qi; Li, Ting; Xiang, Wen-tao; Chen, Chong-bin; Xie, Zheng-yang; Leng, Xue; et al. (Frontiers in Veterinary Science, 2025)
IntroductionBrucellosis is a zoonotic disease that affects both dogs and humans. With the increase in dog ownership, the risk of transmission has risen for both adults and children.MethodsThis study used meta-analysis to comprehensively analyze the prevalence of canine brucellosis in China and to identify the relevant factors affecting its transmission.ResultWe conducted a meta-analysis of 38 studies published between January 1983 and March 2024, sourced from six databases. The results showed a higher prevalence of canine brucellosis in northern and northwestern regions of China, with Xinjiang having the highest prevalence (19.77%) and Hunan the lowest (0.23%). Significant differences were found in positivity rates across different diagnostic methods (P < 0.05), with ELISA yielding the highest positivity rate (11.6%) and PCR and SAT the lowest (3.3%). The positivity rate of stray dogs (22.6%) was significantly higher than that of other dog sources (P < 0.05). Furthermore, environmental factors, such as temperature and altitude, were identified as influencing the incidence of brucellosis.DiscussionIn conclusion, canine brucellosis is prevalent across China, with detection methods, dog sources, and environmental factors contributing to the varying incidence rates. We recommend regular brucellosis testing for pet dogs, improved kennel hygiene, and reduced contact with potentially infected animals.Systematic review registrationhttps://www.frontiersin.org/journals/veterinary-science